Penegakan Hukum Persaingan Usaha dalam Ekonomi Digital Antara KPPU terhadap Google LLC - Yuniar Supu; Weny Almoravid Dungga; Mohamad Hidayat Muhtar (Suara Edukasi Hukum, 2025)
This research discusses the enforcement of business competition law in Indonesia thru a case study of the Business Competition Supervisory Commission (KPPU) against Google LLC in the Google Play Billing System case. The enactment of Law Number 5 of 1999 marked a structural correction to past monopolistic practices, but new challenges emerged in the digital economy, characterized by the dominance of global platforms, network effects, and data power. The KPPU's decision in 2025, which imposed an administrative fine of Rp202.5 billion on Google LLC, proves that competition law is still relevant for regulating modern digital practices, particularly regarding Article 17 on the prohibition of monopoly practices and Article 25 paragraph (1) letter b on the abuse of dominant position. This analysis shows that Google's policy requiring the use of its internal payment system limits consumer choice, hinders local developers, and narrows the space for innovation. This finding confirms that competition law serves as a corrective instrument to protect the public interest while also fostering a healthy business climate. However, the normative limitations of Law No. 5/1999 in addressing the complexities of the digital market create an urgent need for regulatory reform, including the formation of a more precise and adaptive Digital Market Law. This research is expected to enrich academic discourse and serve as a practical reference for strengthening competition law instruments in the face of global technology company dominance.